Career success – the perception of Open Distance Learning library middle managers. Issue 6 (12th August 2019) - Raubenheimer, Janette; Ngulube, Patrick
Abstract : Purpose: The purpose of this paper is to gain original evidence of the perception of Open Distance Learning (ODL) library middle managers towards the meaning of career success from the perspective of the individual. Design/methodology/approach: This quantitative research study was conducted with the help of a survey questionnaire designed by the first researcher. Findings: Results revealed that career success no longer only relates to criteria such as the hierarchical position or progression through high ratings obtained during performance appraisal. A high premium is placed by ODL library middle managers on other success criteria identified in the literature, such as the positive effect of their work on the institution, success achieved through a focus on work life and home life balance and personal recognition due to competence. Research limitations/implications: The research findings presented in this paper form an important part of a comprehensive study on ODL library middle management development but is limited to the only ODL library in South Africa. Practical implications: The paper provides current perceptions of ODL library middle managers to be considered during career path planning. Originality/value: The paper provides the first findings of an overview of the perception of South African ODL library middle managers towards the meaning of career success. The study is timely as the number of ODL institutions is growing. The target population to benefit from this study is ODL library practitioners.